The French Sociology of Art (Origins and Contradictions) - Andrijauskas, Antanas (Problemos, 1987)
The problem of the social conditionality of artistic creation in the French aesthetics and research into art is considered. The theoretical origins of the French sociology of art are traced back, the conceptions of H. Taine, Ch. Lalo and E. Sourieu are examined, and P. Frankastel’s efforts to make the sociology of art scientific are showed. The main trends of the modern sociology are examined too. It is claimed, that the modem French sociology of art on the whole does not deal with the fundamentals of the bourgeois culture and really presents only the more subtle apology of the bourgeois status and art.